The Spectrum of Fundamental Basic Science Discoveries Contributing to Organismal Aging - Farr, Joshua N (J Bone Miner Res, 2018)
Aging research has undergone unprecedented advances at an accelerating rate in recent years, leading to excitement in the field as well as opportunities for imagination and innovation. Novel insights indicate that, rather than resulting from a preprogrammed series of events, the aging process is predominantly driven by fundamental non-adaptive mechanisms that are interconnected, linked, and overlap. To varying degrees, these mechanisms also manifest with aging in bone where they cause skeletal fragility. Because these mechanisms of aging can be manipulated, it might be possible to slow, delay, or alleviate multiple age-related diseases and their complications by targeting conserved genetic signaling pathways, controlled functional networks, and basic biochemical processes. Indeed, findings in various mammalian species suggest that targeting fundamental aging mechanisms (eg, via either loss-of-function or gain-of-function mutations or administration of pharmacological therapies) can extend healthspan; ie, the healthy period of life free of chronic diseases. In this review, we summarize the evidence supporting the role of the spectrum of fundamental basic science discoveries contributing to organismal aging, with emphasis on mammalian studies and in particular aging mechanisms in bone that drive skeletal fragility. These mechanisms or aging hallmarks include: genomic instability, telomere attrition, epigenetic alterations, loss of proteostasis, deregulated nutrient sensing, mitochondrial dysfunction, cellular senescence, stem cell exhaustion, and altered intercellular communication. Because these mechanisms are linked, interventions that ameliorate one hallmark can in theory ameliorate others. In the field of bone and mineral research, current challenges include defining the relative contributions of each aging hallmark to the natural skeletal aging process, better understanding the complex interconnections among the hallmarks, and identifying the most effective therapeutic strategies to safely target multiple hallmarks. Based on their interconnections, it may be feasible to simultaneously interfere with several fundamental aging mechanisms to alleviate a wide spectrum of age-related chronic diseases, including osteoporosis.